Assessment of Anterior Segment Changes in Pseudophakic Eyes, Using Ultrasonic Biomicroscopic Imaging, after Pars Plana Vitrectomy with Silicone Oil or Gas Tamponade - Erkan Ünsal; Kadir Eltutar; Belma Karini; Osman Kızılay (Journal of Ophthalmology)
Objective. To evaluate the morphological changes of the anterior segment using ultrasonic biomicroscopy (UBM) imaging in pseudophakic patients who underwent pars plana vitrectomy (PPV) with silicone oil or gas (C3F8) internal tamponade agent injection. Method. This prospective study included pseudophakic patients with planned PPV, divided into two groups according to internal tamponade agent: those in which silicone oil was used (n=27, Group 1) and those in which gas (C3F8) was used (n=24, Group 2). UBM measurements were performed in the supine position before and one week after surgery. Results. In patients of Group 1, postoperative trabecular meshwork-ciliary process distance (T-CPD) and iris-ciliary process distance (I-CPD), according to preoperative values, were found to be statistically significantly reduced, and postoperative mean value of scleral thickness (ST) and intraocular pressure (IOP), according to preoperative value, was found to be statistically significantly increased. In patients of Group 2, postoperative mean values of anterior chamber depth (ACD), ciliary body thickness (CBT), T-CPD, I-CPD, and IOP, according to preoperative values, were found to be statistically significantly reduced. Preoperatively, in Group 2 patients, according to Group 1 patients, TIA and IOP were found to be statistically significantly increased. Preoperative and postoperative IOP between the measured parameters with UBM showed no statistically significant correlation. Conclusions. Gases cause more morphological changes in the anterior segment structures. It is thought that complications such as increased intraocular pressure can be seen more frequently for this reason.